Rola rachunku kosztów w procesie zarządzania podmiotem gospodarującym - Szadziewska, Arleta (Role of Cost Accounting in the Process of Enterprises Management, 2006)
The evolution of the cost accounting practice depends on existing needs of companies operating on the market. Permanent changes in their business environment affect the introduction of new methods of cost accounting. It is a reason why cost accounting is one of the management tools in an enterprise. The purpose of this paper is to introduce the role of cost accounting in the process of enterprises management. In the competitive market the cost accounting is the base for cost management. It also increases the effectiveness of the decisions making process in short and long term. (
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 587-598